2008
DOI: 10.1007/s00417-008-0792-9
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation therapy in glaucoma surgery

Abstract: The majority of surgeons do not stop warfarin or aspirin prior to glaucoma surgery. There is a great diversity in current practice with regard to the management of anticoagulant therapy prior to glaucoma surgery amongst glaucoma surgeons in England. Currently there is little information available to offer definitive guidance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 17 publications
1
19
0
1
Order By: Relevance
“…We believe the main reason for this difference could be related to the fact that a significant percentage of the participants in our study (approximately half of them) have experienced hemorrhagic compli cations in their anticoagulated patients during or after a glaucoma surgery. Another interesting difference between these two studies is that while most of the interviewees in our study (over 90%) required a cardiologist or a general practitioner opinion when dealing with anticoagulated patients prior to glaucoma surgery (even though there is no official guideline for this), only 23.8% of the respondents from the British survey (5) usually rely on a second opinion (in fact, an hematologist was the specialist required in that study).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…We believe the main reason for this difference could be related to the fact that a significant percentage of the participants in our study (approximately half of them) have experienced hemorrhagic compli cations in their anticoagulated patients during or after a glaucoma surgery. Another interesting difference between these two studies is that while most of the interviewees in our study (over 90%) required a cardiologist or a general practitioner opinion when dealing with anticoagulated patients prior to glaucoma surgery (even though there is no official guideline for this), only 23.8% of the respondents from the British survey (5) usually rely on a second opinion (in fact, an hematologist was the specialist required in that study).…”
Section: Discussionmentioning
confidence: 77%
“…In a previous survey done in the United Kingdom, questionnaires were sent to ophthalmologists with a special interest in glaucoma (5) . Approximately 30% of the respondents stop either warfarin or as pirin, for 4 and 7 days prior to surgery, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multicenter audit has shown that 5.1% of 48,862 patients subjected to cataract surgery were on concurrent warfarin therapy (1) . Considering the long and variable half-life of vitamin K antagonists, some guidelines recommend that patients should discontinue warfarin at least 5 days before major procedures (10)(11)(12) . The incidences of subconjunctival hemorrhage and microscopic hyphema were significantly higher in patients undergoing pha coe mulsification without warfarin interruption compared with the dis continuation subgroup, although most of such bleeds were self-limiting and did not significantly decrease visual acuity (13)(14)(15) .…”
Section: Discussionmentioning
confidence: 99%
“…In der Literatur ist dies für "Marcumar" in einigen Studien nachgewiesen worden, für die Thrombozytenaggregationshemmer bleibt dies umstritten [16 -20]. Viele Autoren sind der Meinung, dass ein Absetzen von ASS vor der Trabekulektomie nicht notwendig ist [17,21]. Eine expulsive Blutung trat in keine der beiden Gruppen intra-oder postoperativ auf, was neben der Sicherheit des opera- …”
unclassified